Stabilization of recycled and pure soils using mussel shell powder and cement: Experimental evaluation of strength and durability - Tugba Eskisar; Esma Rahat (Engineering Science and Technology, an International Journal)
The integration of industrial and biogenic waste materials in soil stabilization provides an environmentally sustainable alternative to conventional binders. This study evaluates the influence of mussel shell powder (MSP) on both untreated, cemented, and recycled soils, where the recycled soil was initially stabilized with calcium carbide residue, cured for one year, ground into powder, and then re-treated with MSP. Unconfined compression, ultrasonic pulse velocity, and direct shear tests were conducted to assess the strength, compaction, and shear behavior of MSP-stabilized pure, recycled, and cemented soils. The results indicate that MSP addition reduced plasticity and improved soil workability. In recycled soils, 5% MSP provided optimal strength enhancement, while in cemented soils, 20% MSP was required for significant strength gains due to its role in secondary cementation. Freeze-thaw tests demonstrated that MSP-treated soils exhibited up to a 40% reduction in strength loss compared to untreated samples, improving durability in cold climates. The ultrasonic pulse velocity measurements showed strong correlations with unconfined compressive strength, confirming its potential as a non-destructive assessment method for stabilized soils. These findings highlight the potential of MSP as a sustainable stabilizer for improving soil mechanical properties, durability, and resistance to freeze–thaw cycles.